(3eNJUQ GdHjGf aj fSH Bd YOfGfs - (3CHh GdYHGS CMeO Hf CHi YHO Gddg eMeO Hf CMeO Hf eMeO (B((3aJMG(B) (3Hf YHO Gddg Hf jMji LRi GdCfOdSjs; (3YHO Gddg Hf YjSi Hf eMeO Hf NdOhf GdJhfSjs
(3ChdgG (B:s
(3GdMeO ddg GdefaQO ai GdPGJ hGdUaGJ hGdCaYGd s
(3BNQgG (B:s
(3hjNJe YdjfG HGdMSfi HLGg SjOfG hehdGfG eMeO Udi Gddg Ydjg hSde hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B134(3C (B- (3U(B190(3Cs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B369 s
Keywords: (3GdJGQjNs